Analisis Konsep Non Maleficience pada Pasien dengan Diabetes Melitus - Caryanto, Valerio Basuni Carlo; Awaludin, Sidik (Journal of Bionursing, 2025)
Background. Non-maleficence is an ethical principle in the field of nursing. This concept is often used in patient care in carrying out or providing nursing actions. Non-maleficence in patients with diabetes mellitus refers to actions that do not cause harm or harm to the patient Methods. Analyze this concept carried out with the help of literature on non-maleficence obtained throughGoogle Scholar and Online Books database. The keywords used are "Concept of non-maleficence" and "diabetes mellitus patients". Year of publication of books and articles used from 1979 to 2023. Results. In Indonesia, DM is the 3rd largest cause of death with a percentage of 6.7 percent, after stroke, which is 21.1 percent, and heart disease, which is 12.9 percent. In 2013, the prevalence of DM in Indonesia was 1.5%, while in 2018 it reached 2.0%. Based on age categories, the largest number of DM sufferers are in the age range 55-64 years and 65-74 years. In addition, more DM sufferers in Indonesia are women (1.8%) than men (1.2%). Then, for areas of residence, more diabetes mellitus sufferers are in urban areas (1.9%) compared to rural areas (1.0%) Conclusion. Concept analysis was carried out using the methods and steps proposed by Walker and Avant 2011. Methods of identifying the attributes, antecedents and consequences of nonmaleficence. Non Maleficence is an ethical obligation not to cause harm intentionally or through negligence without any justifiable reason, the principle of action should be in accordance with procedures to ensure safety considering benefits.